1) тут можно выразить одну переменную через другую.
2у=14-7х
у=14-7х/2=7-7х
-7х=-7
х=1
либо:
7х=14-2у
х=14-2у/7=2-2у
-2у=-2
у=1.
2) тут просто подставляешь значения в само уравнение:
-3*(-5)+3=18
18=18
подходит!
-3*(-3)+3=18
12=18
не подходит!
2*10-2=18
1) тут можно выразить одну переменную через другую.
2у=14-7х
у=14-7х/2=7-7х
-7х=-7
х=1
либо:
7х=14-2у
х=14-2у/7=2-2у
-2у=-2
у=1.
2) тут просто подставляешь значения в само уравнение:
-3*(-5)+3=18
18=18
подходит!
-3*(-3)+3=18
12=18
не подходит!
2*10-2=18
18=18
подходит!